GCSE Chemistry Homework Book - McDuell, Bob (Letts Educational, 1997)
This GCSE Chemistry homework book is designed to be used with the accompanying classbook. It contains 46 homework units, Each of which has a summary of the main points covered in the classbook with homework questions of varying difficulty. The homework book also contains a bank of GCSE-style reviw questions for revision and exam as well as a comprehensive glossary of terms.
Keywords: Non-Fiction